STRATEGIC ROLE OF HUMAN RESOURCES MANAGEMENT FOR SUSTAINABILITY IN CHEMICAL ENTERPRISES - Marinov, Miroslav (E-Journal VFU, 2025)
This article analyzes the strategic role of Human Resources Management (HRM) in achieving Sustainability (ESG) in the Bulgarian chemical industry. In a sector characterized by high operational risk and strict regulations, HRM is a vital factor in managing the social and governance dimensions of ESG. It is established that traditional HR practices are inadequate for addressing the specific needs of the industry—mandatory safety, intensive qualification, and green skills. HRM must transform into a strategic partner through human capital planning, systems for continuous learning, and the integration of performance evaluation with ESG objectives. The use of ERP is vital for tracking qualifications and managing risk.